UJI AKTIVITAS ANTIHIPERURISEMIA EKSTRAK ETANOL DAUN GEDI HIJAU (Abelmoschus manihot (L.) Medik) PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) (PHARMACON, 2019)
ABSTRACTIn the southeast Asian Region showing prevalence for the incidence of hyperuricemia, Indonesia ranks second with 18%. Diseases resulting from hyperuricemia (Excess uric acid) are known as gout. The use of excessive or uric acid lowering drugs such as Allopurinol can cause side effects. Flavonoids are known to inhibit xanthine oxidase, so flavonoids have the potential to be used as antyhiperuricemia agents. Green gedi leaves that have been extracted with 96% ethanol have a total flavonoid content of 41.56%. This study aims to determine the potential activity of reducing uric acid levels from green gedi leaves. This type of research is an experimental study carried out in a laboratory with rat test animals with 5 kind of treatments with 3 treatments per repetition. Hyperuricemia conditioning is done by inducing potassium oxonate intraperitoneally. Group I as negative control was given 1% CMC, group II as positive control was given Allopurinol, group III-V was treated with ethanol extract of green gedi leaves with defferent doses of 3.6mg, 7.2mg and 14.4mg. Based on the ANOVA test results obtained there is a significantly different levels of uric acid with p = 0.038 (